2014
DOI: 10.1021/cb500515r
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitors of SETD8 with Cellular Activity

Abstract: SETD8/SET8/Pr-SET7/KMT5A is the sole protein lysine methyltransferase (PKMT) known to monomethylate lysine 20 of histone H4 in vivo. SETD8’s methyltransferase activity has been implicated in many essential cellular processes including DNA replication, DNA damage response, transcription modulation, and cell cycle regulation. Developing SETD8 inhibitors with cellular activity is a key step toward elucidating the diverse roles of SETD8 via convenient pharmacological perturbation. From the hits of a prior high thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 41 publications
4
79
0
Order By: Relevance
“…The IVTI of UNC0379 in NB cells was highly significant when compared with normal cells, suggesting that its characteristics warrant further development. The recent elucidation of structure-activity relationships among SETD8 inhibitors (Ma et al, 2014b) and the identification of other small-molecule inhibitors of SETD8 (Blum et al, 2014) should lead to compounds with increased activity and selectivity (A. Ma unpublished data). As with many targeted compounds, combination studies may prove more efficacious and further studies of inhibitors of SETD8 with Nutlin-3 or DNA damaging conventional cytotoxic agents will be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The IVTI of UNC0379 in NB cells was highly significant when compared with normal cells, suggesting that its characteristics warrant further development. The recent elucidation of structure-activity relationships among SETD8 inhibitors (Ma et al, 2014b) and the identification of other small-molecule inhibitors of SETD8 (Blum et al, 2014) should lead to compounds with increased activity and selectivity (A. Ma unpublished data). As with many targeted compounds, combination studies may prove more efficacious and further studies of inhibitors of SETD8 with Nutlin-3 or DNA damaging conventional cytotoxic agents will be explored.…”
Section: Discussionmentioning
confidence: 99%
“…22 A set of quinone compounds were reported as cell-active inhibitors of SETD8. 23 The quinones covalently modified one or more residues on SETD8. Given that the quinone moiety is redox-active and that quinones are known to be promiscuous assay-interference compounds, 24 these compounds may have off-target activities.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory activity was confirmed in as eries of orthogonal biochemical andb iophysical assays. [33] Dose-response curves determined by as econdary radiometricf ilter paper assay confirmedt he three compounds SPS8I1-3 (small-molecule pool of SETD8 inhibitor,F igure 9; SPS8I1, also known as NSC663284; SPS8I2, also as known as BVT948;S PS8I3,k nown as ryuvidine) as potent inhibitors of SETD8, with apparent IC 50 values of 0.21 AE 0.03, 0.50 AE 0.20, and 0.70 AE 0.20 mm,r espectively.T he selectivities of these compounds were evaluated against ap anel of representative human methyltransferases, including six KMTs( SETD2, GLP,G 9a, SETD8, SMYD2, and SETD7) and three protein arginine methyltransferases (CARM1, PRMT1,a nd PRMT3). Jin and co-workers also synthesized af ew analogues of UNC0379 and studied the structure-activity relationships of the quinazoline scaffold.…”
Section: Unc0379mentioning
confidence: 99%
“…Mechanism of action (MOA) studies, performed by investigating SETD8 inhibition with varying concentrationso f the H4 peptides ubstrate or the cofactor SAM, indicated that UNC0379 was competitive with the peptidesubstrate and noncompetitive with the cofactor.M oreover,s electivity assays showed that the inhibitor was selectivef or SETD8 over 15 other methyltransferases, including G9a and GLP,t he two KMTs that are effectively inhibited by quinazolines. [33] All three inhibitors contained aM ichael acceptor quinonic motif (indicated in red in Figure 9) that could react with active cysteiner esidues.T herefore, the authors performed further mechanistic studies that showed that SPS8I1-3i nhibited SETD8 through an irreversible slow-onset process. [32] They found that the terminal pyrrolidineg roup at the 4position wasw ell tolerated, whereas modifications of length and/ornature of the 5-carbonlinker weredetrimental;m odifications at the 2-position were generally not tolerated, with the only exceptiono ft he replacement of thep yrrolidine with ad imethylamino group;am ethoxy or ethoxy group was required at the 6-position, and replacement with an hydrogen or with al arger group or al ess electron-donating group was disfavored;m odifications at the 7-position could be well tolerateda nd could, eventually, lead to more potent SETD8 inhibitors.…”
Section: Unc0379mentioning
confidence: 99%